Age-related EMG responses of the biceps brachii muscle of young adults. - Ahamed, Nizam Uddin; Alqahtani, Mahdi; Rahman, Matiur (Biomedical India, 2016)
Although the effect of an Electromyographic (EMG) signal on the Biceps Brachii (BB) muscle is at the forefront of human movement analysis, there is limited information regarding the importance of the differences in the age-related EMG responses during contraction. The present study aimed to compare the BB muscle activity of three different groups of young adults divided based on age and to find a relationship between surface EMG and endurance time during isometric contraction. The EMG signal was recorded in 30 healthy right-arm-dominant young male subjects during a handgrip force task. The subjects were rationally divided into one of the three age groups (ten in each group): adolescents (‘A’; aged 17.3 ± 1.4 years), vicenarians (‘V’; 24.6 ± 2.1 years), and tricenarians (‘T’; 33.2 ± 1.1 years). The muscle activation during contraction was determined as the root mean square (RMS) EMG signal normalised to the peak RMS EMG signal during a 10-s isometric contraction. The statistical analysis included linear regression to examine the relationship between the EMG amplitude and the endurance time based on five levels of contraction [60%, 70%, 80%, 90% and 100% of the maximal voluntary contraction (MVC)], repeated measures ANOVA to assess differences among the different age groups and the coefficient of variation (CoV) to investigate the steadiness of the EMG activation. The result shows that the early age groups exhibit higher and steadier muscle activity (V: 3.65 ± 0.42 mV, 11.46% and A: 3.12 ± 0.29 mV, 9.29%) compared with the elderly subjects (T: 2.78 ± 0.33 mV, 11.98%). The most important finding is that the linear slope coefficient for the EMG (amplitude) as a function of time for the muscle of the ‘V’ group (r2=0.591, P<0.05) was significantly greater compared those found for the muscles of the ‘T’ (r2=0.152, P>0.05) and ‘A’ groups (r2=0.203, P > 0.05). The results obtained in this study can be used to improve the current understanding of the mechanics and muscle functions of the BB muscle of individuals from different age groups during isometric contraction.